Optimized PID Controller for Propofol and Remifentanil Coadministration: Influence of Opioid-Hypnotic Balance. Issue 15 (2021) - Schiavo, Michele; Padula, Fabrizio; Latronico, Nicola; Paltenghi, Massimiliano; Visioli, Antonio
Abstract: In the practice of total intravenous anesthesia, the regulation of the balance between opioid and hypnotic drugs is fundamental since it has a significant impact on depth of hypnosis and hemodynamics. Therefore, in the implementation of a fully automated control system for anesthesia, this aspect must be considered. In a recently devised PID-based control scheme for propofol and remifentanil coadministration, the opioid-hypnotic balance is handled by imposing a ratio between the infusion rates of these two drugs. The anesthesiologist can choose the most suitable balance during each phase of surgery by changing the ratio. The aim of this paper is to evaluate and discuss the benefits that this solution can bring in the clinical practice. In order to do so, the proposed solution has been tested in simulation by using a recently devised open source patient simulator that takes into account both anesthetic and hemodynamic variables. Simulation results show that the proposed approach automatically induces and maintains the desired depth of hypnosis and, furthermore, it gives the anesthesiologist the possibility to better manage the patient's hemodynamics by selecting the most appropriate opioid-hypnotic balance for each situation.